Analysis on the Optimization of Agricultural Products Logistics in Huairen City. Issue 4 (March 2020) - Li, Dandan; Hou, Hanping; Yang, Jianliang; Yao, Tianhui; Zhang, Kexin; Liu, Xinlu; Ren, Hongzhi; Wang, Wenjuan; Wang, Liting
Abstract: The essence of agricultural products logistics is the entity flow and information transfer from producer to consumer, which not only meets the needs of customers, but also realizes the value of agricultural products. Huairen city has a huge demand for the modernization of agricultural products logistics because of its natural location advantage and the active guidance of national policies. Although the city has made progress in the construction of transportation facilities and logistics industry, there are still problems such as backward level of cold chain logistics, low level of standardization and informatization, and shortage of talents. Therefore, based on the theory and practice, this paper analyzes the current situation, explores the future development direction of Huairen city's agricultural products logistics, so as to accelerate the establishment of a modern agricultural products circulation system, promote the rationalization and adjustment of the agricultural structure.